The role of ICT in companies (Docentes 2.0 Journal, 2013)
The approach of ICTs to companies begins with awareness and awareness, raising awareness of the opportunities and benefits of ICTs and proposing solutions tailored to small and large companies. ICTs are a tool at the service of the company; They are a means never an end. Incorporating ICT in companies often implies adopting new ways of working and sometimes also new business models.
Keywords: ICT; company; role